Associations between teachers’ beliefs and their perception of hate speech in school: a study in Germany and Switzerland - Kansok-Dusche, Julia; Wettstein, Alexander; Fischer, Saskia M.; Wachs, Sebastian; Bilz, Ludwig (Frontiers in Education, 2024)
Hate speech is a global issue that is also prevalent among adolescents and requires an educational response. Teachers handle hate speech as part of their professional role. To date, we know little about their beliefs in relation to the early stages of their interventional actions, specifically to their perception of hate speech in school. Thus, this study examined associations between teachers’ social dominance orientation, their pluralist attitude, and their hate speech perception in school. A sample of 471 secondary school teachers from 38 schools (Germany: n = 251; Switzerland: n = 220) participated in a self-report survey from December 2020 to April 2021 (MAge = 42.8 years; 57.7% females; 21.0% with migration status). Data from a total of 3,560 students from grades 7–9 (Germany: n = 1,841; Switzerland: n = 1,719) were matched with teachers’ data to control for students’ hate speech perception in school. Fixed effects multilevel regressions were run, including covariates (teachers’ age, gender, migration status, students’ hate speech perception), teachers’ social dominance orientation, pluralist attitude, and their hate speech perception in school. Teachers perceived a higher frequency of offline hate speech than online hate speech. Contrary to the hypotheses, social dominance orientation was positively associated with offline and online hate speech perception. As predicted, teachers’ pluralist attitude was positively linked to their off- and online hate speech perception. Further research must now clarify how the investigated beliefs and attitudes and teachers’ hate speech perception in school relate to other aspects of their professional competence.